2020
DOI: 10.33448/rsd-v9i9.8207
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização bromatológica e perfil fermentativo de silagem de capim elefante misturada com ingredientes alternativos

Abstract: Objetivou-se avaliar a composição bromatológica, perfil fermentativo e perdas fermentativas da silagem de capim elefante (CE) adicionado com diferentes níveis de palma forrageira (PF) e torta de semente de cupuaçu (TSC). Adotou-se o delineamento inteiramente casualizado (DIC), em esquema fatorial 2x3+2, com cinco repetições cada, totalizando 40 mini silos experimentais, com armazenamento por 50 dias. Avaliaram-se oito tratamentos, um composto somente por CE, um pool contendo 40% de CE, 30% de TSC e 30% de PF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
0
0
1
Order By: Relevance
“…A cada 1% de inclusão de palma ocorreu um decréscimo de 1,89 g/kg de MS. Essa redução nos níveis de MS em resposta a substituição do farelo de sorgo por palma forrageira está relacionada ao baixo teor de matéria seca encontrado na palma (6,89 %), o que resultou em uma variação entre 384,8 g/kg para os níveis 0% até 193,4 g/kg para os níveis 100% de substituição (Tabela 1). A palma de um modo geral apresenta um alto teor de umidade (Borges et al, 2020).…”
Section: Resultsunclassified
“…A cada 1% de inclusão de palma ocorreu um decréscimo de 1,89 g/kg de MS. Essa redução nos níveis de MS em resposta a substituição do farelo de sorgo por palma forrageira está relacionada ao baixo teor de matéria seca encontrado na palma (6,89 %), o que resultou em uma variação entre 384,8 g/kg para os níveis 0% até 193,4 g/kg para os níveis 100% de substituição (Tabela 1). A palma de um modo geral apresenta um alto teor de umidade (Borges et al, 2020).…”
Section: Resultsunclassified
“…The highest soluble carbohydrate contents that were found in the silages with 100% fruit (Table 3) are attributed to the melon fruit that has high concentrations of soluble carbohydrates, which favors the growth of yeasts due to the excess of substrates for their development, since according to several studies, it is known that contents of 6 to 8% of soluble carbohydrates are sufficient for an adequate microbial fermentation [34]. However, the high amount of soluble sugars can result in higher levels of lactic acid and residual soluble carbohydrates, and there may be a predominance of yeasts, which results in alcoholic fermentation [7], which in turn, can result in losses of DM and low aerobic stability of the silage.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to determine the inclusion levels of cactus in association with fibrous feeds, especially for silage production, due to its high moisture content. Borges et al (2020) reported relevant effects when studying cactus and elephant grass mixed silages, with increases in the contents of residual soluble carbohydrates and a decrease in pH with the inclusions of 20, 40, and 60% of cactus.…”
Section: Introductionmentioning
confidence: 99%